2013
DOI: 10.1186/1757-7241-21-59
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a percutaneous device and the bougie-assisted surgical technique for emergency cricothyrotomy: an experimental study on a porcine model performed by air ambulance anaesthesiologists

Abstract: BackgroundA large number of techniques and devices for cricothyroidotomy have been developed. In this study, the Portex™ Cricothyroidotomy Kit (PCK, Smiths Medical Ltd, Hythe, UK) was compared with the bougie assisted emergency surgical cricothyrotomy technique (BACT).MethodsTwenty air ambulance anaesthesiologists performed emergency cricothyrotomy on a cadaveric porcine airway model using both PCK and BACT. Baseline performance and performance after the intensive training package were recorded. Success rate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…Although we showed a difference in speed of securing an airway with a palpable vs. an impalpable membrane, the timings for the latter were still acceptable, demonstrating the positive effect of training. Both sets of times are comparable to those found by other groups investigating broadly similar bougie-assisted cricothyroidotomy techniques [10][11][12][13], with average procedural times of 33-81 s. Our study, however, is probably the first evaluation of the FONA techniques described in the DAS 2015 guidelines in a benchtop study and showed a high first-attempt success rate.…”
Section: Discussionsupporting
confidence: 85%
“…Although we showed a difference in speed of securing an airway with a palpable vs. an impalpable membrane, the timings for the latter were still acceptable, demonstrating the positive effect of training. Both sets of times are comparable to those found by other groups investigating broadly similar bougie-assisted cricothyroidotomy techniques [10][11][12][13], with average procedural times of 33-81 s. Our study, however, is probably the first evaluation of the FONA techniques described in the DAS 2015 guidelines in a benchtop study and showed a high first-attempt success rate.…”
Section: Discussionsupporting
confidence: 85%
“…21 Using simulations as a tool to identify different treatment and decision-making strategies is not new. Simulation has been used to test new healthcare facilities and to identify potential flaws, 22 to test procedure competence and 23 and to evaluate protocol and team performance. 24 In the context of our study, the simulation acted as a tool to identify strategies for EOL decisions.…”
Section: Medical Simulationmentioning
confidence: 99%
“…Expert opinion, NAP4, and difficult airway society (DAS) guidelines do not recommend small‐bore catheters or uncuffed cannulas in inexperienced hands because of possible serious complications. At the time of the survey there was no gold standard for a cricothyrotomy technique, but surgical FONA was associated with better success rates than percutaneous techniques . The scalpel bougie method might be an interesting alternative to a percutaneous technique for ENT surgeons, since it is based on skills that they are already familiar with.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of the survey there was no gold standard for a cricothyrotomy technique, 1,8 but surgical FONA was associated with better success rates than percutaneous techniques. 3,9,10 The scalpel bougie method 11,12 might be an interesting alternative to a percutaneous technique for ENT surgeons, since it is based on skills that they are already familiar with. Moreover, this technique uses materials readily available (scalpel, introducing catheter, cuffed tube 6).…”
Section: Materials and Protocolsmentioning
confidence: 99%